2021
DOI: 10.3390/pathogens10020207
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium accolens Has Antimicrobial Activity against Staphylococcus aureus and Methicillin-Resistant S. aureus Pathogens Isolated from the Sinonasal Niche of Chronic Rhinosinusitis Patients

Abstract: Corynebacterium accolens is the predominant species of the healthy human nasal microbiota, and its relative abundance is decreased in the context of chronic rhinosinusitis (CRS). This study aimed to evaluate the antimicrobial potential of C. accolens isolated from a healthy human nasal cavity against planktonic and biofilm growth of Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus (MRSA) clinical isolates (CIs) from CRS patients. Nasal swabs from twenty non-CRS control subjects were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…accolens incidence was significantly decreased in the URT of patients with SARS-CoV-2 compared with uninfected controls ( Mostafa et al., 2020 ). Corynebacterium accolens can inhibit Streptococcus pneumoniae and Staphylococcus aureus growth, possibly through triolein hydrolysis, which releases oleic acid ( Bomar et al., 2016 ; Menberu et al., 2021 ). In addition to inhibiting bacterial pathogens, oleic acid is capable of inhibiting other enveloped viruses, such as herpes and influenza ( Kohn et al., 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…accolens incidence was significantly decreased in the URT of patients with SARS-CoV-2 compared with uninfected controls ( Mostafa et al., 2020 ). Corynebacterium accolens can inhibit Streptococcus pneumoniae and Staphylococcus aureus growth, possibly through triolein hydrolysis, which releases oleic acid ( Bomar et al., 2016 ; Menberu et al., 2021 ). In addition to inhibiting bacterial pathogens, oleic acid is capable of inhibiting other enveloped viruses, such as herpes and influenza ( Kohn et al., 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the exact shift in Corynebacterium population during AD disease course is still unknown, several studies have identified the ability of Corynebacterium spp including striatum, pseudodiphtheriticum and accolens to inhibit SA growth and virulence. [94][95][96] The precise inhibitory Commensals Anti-Staphylococcus aureus mechanism Reference…”
Section: S Epidermidis Has Been Shownmentioning
confidence: 99%
“…to inhibit the growth and colonization of pathobionts in the respiratory tract. C. accolens can inhibit S. pneumoniae via liberation of free fatty acids from triacylglycerols found on the skin (Bomar et al, 2016), and clinical isolates of C. accolens can inhibit the growth of methicillin resistant S. aureus (Menberu et al, 2021). C. pseudodiphtheriticum is inhibitory against M. catarrhalis and S. aureus (Hardy et al, 2019;Lappan, 2019).…”
Section: Dolosigranulum Pigrum and Corynebacterium Sppmentioning
confidence: 99%